Negative Affect Is Associated With Higher Risk of Incident Cognitive Impairment in Nondepressed Postmenopausal Women. (19th September 2017) - Korthauer, Laura E; Goveas, Joseph; Espeland, Mark A; Shumaker, Sally A; Garcia, Katelyn R; Tindle, Hilary; Salmoirago-Blotcher, Elena; Sink, Kaycee M; Vaughan, Leslie; Rapp, Stephen R; Resnick, Susan M; Driscoll, Ira
Abstract: Background: Positive affect (PA) and negative affect (NA) reflect subjective emotional experiences. Although related to depression and anxiety, these dimensions are distinct constructs representing affective states and patterns. Prior studies suggest that elevated depressive symptoms are associated with risk of mild cognitive impairment (MCI) and probable dementia, but whether affective states are associated with cognitive impairment is still unknown. The present study examined relationships between baseline affective states and cognitive impairment (MCI, probable dementia) in nondepressed women. Method: Baseline PA and NA were assessed in postmenopausal women ( N = 2, 137; mean age = 73.8 years) from the Women's Health Initiative Study of Cognitive Aging (WHISCA) using the Positive and Negative Affect Schedule (PANAS). Women were followed annually for an average of 11.3 years; those with elevated depressive symptoms at baseline were excluded. Results: Higher NA was associated with a higher risk of MCI and probable dementia, even after adjusting for important covariates including age, education, sociodemographic, lifestyle, and cardiovascular risk factors, global cognition, and hormone therapy assignment at baseline. PA was not significantly associated with either outcome. Conclusions: We present the first evidence to date that greater NA, even in the absence of elevated depressive symptoms, is associated with higher risk of MCI and dementia. This suggests that NA may be an important, measureable and potentially modifiable risk factor for age-related cognitive decline.